Weather conditions affect spring migration departure of Ruddy-headed Goose in the southern Pampas, Argentina - Pedrana, Julieta; Gorosabel, Antonella; Kazimierski, Laila Daniela; Pütz, Klemenes; Bernad, Lucia; Laneri, Karina Fabiana (Wiley, 2022)
Fil: Pedrana, Julieta. Universidad Tecnológica Nacional; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina